Low-Complexity Distortionless Techniques for Peak Power Reduction in OFDM Communication Systems. (15th August 2012) - Ghassemi, A.; Gulliver, T. A.
Abstract : A high peak-to-average power ratio (PAPR) is one of the major drawbacks to using orthogonal frequency division multiplexing (OFDM) modulation. The three most effective distortionless techniques for PAPR reduction are partial transmit sequence (PTS), selective mapping (SLM), and tone reservation (TR). However, the high computational complexity due to the inverse discrete Fourier transform (IDFT) is a problem with these approaches. Implementation of these techniques typically employ direct computation of the IDFT, which is not the most efficient solution. In this paper, we consider the development and performance analysis of these distortionless techniques in conjunction with low-complexity IFFT algorithms to reduce the PAPR of the OFDM signal. Recently, proposed IFFT-based techniques are shown to substantially reduce the computational complexity and improve PAPR performance.